Answer:
Given that,
![\begin{gathered} f(x)=x^2 \\ g(x)=x-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ttw3edo74ql26gt1oqf60nq4rnopvqcvi3.png)
To find,a. (fog)(x)
b. (gof)(x)
c. (fog)( - 1)
d. (gof)( - 1)
we know that,
The composition of a function is an operation where two functions say f and g generate a new function say h in such a way that h (x) = g (f (x)). It means here function g is applied to the function of x that is f(x).
It is represented as (gof)(x), i.e)
![(g\circ f)(x)](https://img.qammunity.org/2023/formulas/mathematics/college/ja84bll6zkpk9965ixckom7f6axmzez9z2.png)
a)(fog)(x)
![(f\circ g)(x)=f(g(x))](https://img.qammunity.org/2023/formulas/mathematics/college/qytlfzimoxtv7qpo9rm3ru8joolfgz0nxs.png)
![=f(x-6)](https://img.qammunity.org/2023/formulas/mathematics/college/3s92yz01kp0yqyvn4oxbuen8xw2r7u2wzn.png)
Put x=x-6 in the function f(x),
![=(x-6)^2](https://img.qammunity.org/2023/formulas/mathematics/college/h58xqmih5u8klybye9rufa9xtrq6pwthbo.png)
we get,
![(f\circ g)(x)=(x-6)^2-----(1)](https://img.qammunity.org/2023/formulas/mathematics/college/eby0h80aus1ay0eovv7nuzl066w9sueijq.png)
b)(gof)(x)
![(g\circ f)(x)=g(f(x))](https://img.qammunity.org/2023/formulas/mathematics/college/8lu2o6klwimn8usrejj4tq4ax3gg3hc8p3.png)
![=g(x^2)](https://img.qammunity.org/2023/formulas/mathematics/college/yt7tpx3unkmsdj1gl8zb0dfzlbsazu2hl3.png)
Put x=x^2 in the function g(x),
![=x^2-6](https://img.qammunity.org/2023/formulas/mathematics/college/joaf0lzpipog6sx55c6a1f0j0pjerzizch.png)
we get,
![(g\circ f)(x)=x^2-6----(2)](https://img.qammunity.org/2023/formulas/mathematics/college/rn9daacmzha8zlduaam0uf0ehsi10j1soh.png)
c) (fog)( - 1)
using equation (1), Put x=-1, we get
![(f\circ g)(-1)=(-1-6)^2](https://img.qammunity.org/2023/formulas/mathematics/college/ayfwtka4pebp48kcx3xja32bprvhfdsfy6.png)
![=(-7)^2=49](https://img.qammunity.org/2023/formulas/mathematics/college/aimbixco2g7381re9rp48fe12jxbaovrwf.png)
![(f\circ g)(-1)=49](https://img.qammunity.org/2023/formulas/mathematics/college/eg0rxrwqxfuk6ukdwpupd12aaxozyobfqb.png)
d) (gof)( - 1)
using the equation (2), Put x=-1, we get
![(g\circ f)(-1)=(-1)^2-6](https://img.qammunity.org/2023/formulas/mathematics/college/2ftx5b5gbtczr37vlu4lm7rrqv0qpn7za2.png)
![=1-6=-5](https://img.qammunity.org/2023/formulas/mathematics/college/21lvzmwcsfsyt0yrr29l3qlc6s0l9a2rib.png)
![(g\circ f)(-1)=-5](https://img.qammunity.org/2023/formulas/mathematics/college/qz6o506umh2f0e07urbxs74rb8bvcwnnl3.png)